Neodesenvolvimentismo e conflitos socioambientais: o caso de Belo Monte - Gilbert, Caroline Marie Abrahão Salomão (2016)
Our object of study is the conflict around the construction of Belo Monte Dam in Xingu River in the state of Pará. Planed to be the third biggest hydroeletricpower plant in the world in one of the most important Amazonian socioecological system, is a product of the governmental Plans to Accelerate Growth (PAC) witch at his turn integrates the Initiative for the Integration of Regional Latin-America Infrastructure. Our objective is to evaluate the development of the actual dam project compared to that other one from the 80’s, when it was first presented to the Brazilian society. The reason why we consider important to study the case is that it´s a huge project witch demands an investment of R$ 30 billion (financed in 80% by public, or, tax money) generating great social environment impacts. One of our hypothesis is that the project, elaborated in a military development agenda, is now inserted in a new context, but still a development one, but a neodevelopment context. Our second hypothesis is that, due to the period it was elaborated (military dictature) and the strong criticisms it received back in 1989, and still does in the present time, there would be some traces like lack of democracy in the way the government and his agencies conducted back then and are conducting now the environmental licensing of the dam. In a context where Brazilian sensibility to environmental problems is increased. The methodology of the study consisted in the research oh bibliographic studies, besides the classes followed in the Post-Graduation Department of Geography of the Pontíficia Universidade Católica de São Paulo